The Critical Roles of Educational, Esthetic, and Authenticity Factors as Determinants of Revisit Intention Through Tourist Satisfaction Bandung Geological Museum - Az Zahra Saskya; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Through visitor satisfaction, this study seeks to determine how educational, esthetic, tour guide, and authenticity elements affect visitors' intentions to return to the Bandung Geological Museum. In order to explain how educational tourism experiences affect tourist satisfaction and, consequently, encourage the intention to return, this study is grounded in expectation confirmation theory. 121 visitors to the Bandung Geological Museum participated in this study, which used a quantitative survey method. A questionnaire was used to gather the data, and partial least squares structural equation modeling was used for analysis. The findings show that the effects of educational, esthetic, and authenticity elements on the intention to return are mediated by visitor satisfaction. These results should help the Bandung Geological Museum's administration prioritize improving authenticity, esthetic appeal, and educational value in order to increase visitor satisfaction, which in turn affects the intention to return. The results of this study show that revisit intention in the context of educational tourism cannot yet be fully explained by the research model. In order to obtain a more thorough understanding of the factors influencing revisit intention, future researchers may expand the research model by adding additional pertinent variables consistent with the features of educational tourism and testing the model's consistency across various destination contexts.